Surgical Management of Incarcerated Bubonoenterocele in a Spitz Dog - A Success Report - Sumiran, N.; Sudarshan, L. Siva; Anjali, K.; Jeevanraj, G. David (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
An inguinal hernia, also called as bubonocele is a protrusion of an organ or part of an organ, fat or tissue through the inguinal ring, i.e. the region in the groin where the abdominal musculature meets the hind legs (Byers et al., 2007). Inguinal hernia may be classified as direct or indirect inguinal hernia, congenital or acquired inguinal hernia, unilateral or bilateral inguinal hernia and traumatic or non-traumatic inguinal hernia. Contents of the inguinal hernia include omentum, fat, ovary, uterus, small intestine, colon, bladder or spleen (Kumar et al., 2020). Clinical signs often reflect the size of the hernia and the hernial contents and range from painless inguinal mass to signs related to incarcerated or nonviable small intestine (Waters et al., 1993). The present report describes the successful surgical management of unilateral incarcerated inguinal enterocele in a dog.
Keywords: musculature meets; omentum; inguinal hernia; enterocele